Solve the system of linear equations using substitution. \( \begin{array}{l}y=6 x-14 \\ y=-8 x \\ \text { Solution }\end{array} \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve the system of equations using substitution, we start with the two equations given: 1. \( y = 6x - 14 \) 2. \( y = -8x \) Since both equations are equal to \( y \), we can set them equal to each other: \[ 6x - 14 = -8x \] Next, we'll solve for \( x \) by getting all terms involving \( x \) on one side: \[ 6x + 8x = 14 \] \[ 14x = 14 \] \[ x = 1 \] Now that we have \( x \), we can substitute it back into one of the original equations to find \( y \). We'll use the second equation: \[ y = -8(1) = -8 \] Thus, the solution to the system of equations is: \( (x, y) = (1, -8) \)